Pelatihan dan Uji Kompetensi Ujian Nasional Desain Web Tingkat di SMK Teladan Pematangsiantar - Rafiqa Dewi; Widodo Saputra (Forum Kerjasama Pendidikan Tinggi, 2021)
Web design is usually applied to digital media such as websites. This will relate to web development which is the development of a website that demands functionality and requires the essence of art in design. Indirectly, this website design includes the terms used in making designs. Focus on the appearance, but will not eliminate the main function of the website that is being designed. Able to provide additional convenience for visitors and website readers. For the purpose of making your own web design by becoming one of the communication media. This goal will convey information in real time and quickly. Meanwhile, in making your own design, the website requires special skills. Therefore, web design training is deemed necessary to be applied to entities that concentrate in the field of software engineering since school age. The training and competency test for the National Examination is carried out using the method of delivering lectures on web design material, questions and answers and discussions, practicum and evaluation of the results of the practicum.